Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Identification of quantitative trait loci (QTL) for resistance to Fusarium crown rot (Fusarium pseudograminearum) in multiple assay environments in the Pacific Northwestern US - G. J. Poole; R. W. Smiley; T. C. Paulitz; C. A. Walker; A. H. Carter; D. R. See; K. Garland-Campbell (Theoretical and Applied Genetics, 2012)

Influence of spatial resolution on assessing channelization impacts on fish and macroinvertebrate communities in a warmwater stream in the southeastern United States - Peter C. Smiley; Eric D. Dibble (Environmental Monitoring and Assessment, 2008)

Implications of a Hierarchical Relationship Among Channel Form, Instream Habitat, and Stream Communities for Restoration of Channelized Streams - Peter C. Smiley Jr.; Eric D. Dibble (Hydrobiologia, 2005)

Patterns of Avian Nest Predators and a Brood Parasite Among Restored Riparian Habitats in Agricultural Watersheds - Jonathan D. Maul; Peter C. Smiley; Charles M. Cooper (Environmental Monitoring and Assessment, 2005)

Attraction of two lacewing species to volatiles produced by host plants and aphid prey - J. Zhu; J. J. Obrycki; Samuel A. Ochieng; Thomas C. Baker; J. A. Pickett; D. Smiley (The Science of Nature, 2005)

Comparative Responses of Parasitoids to Synthetic and Plant-Extracted Nepetalactone Component of Aphid Sex Pheromones - R. T. Glinwood; Y.-J. Du; D. W. M. Smiley; W. Powell (Journal of Chemical Ecology, 1999)